Narrative Policy Framework (NFP) Electronic System Operator Policy: Surveillance and Cyber Security - Ambar Alimatur Rosyidah; Farah Fajriyah (Institute of International Studies, 2022)
Indonesia, as one of the Global South countries, has responded to digital transformation by launching the policy of the Minister of Communication and Information Technology Number 5 of 2020 concerning the Implementation of Private Electronic Systems (ESO) for the realization of digital sovereignty. The policy reaped negative sentiments from the public. Several articles considered ‘rubber articles’ indicated to weaken human rights in obtaining and conveying information, as stated in Article 28F of the 1945 Constitution. This study aims to understand the narrative of digital sovereignty built by Kominfo in the ESO policy and strategies to strengthen that narrative. The research method uses a qualitative approach to the Narrative Policy Framework (NFP) by collecting reliable online data from the official Kominfo website, online media, and press conference videos. This study was studied using Agency Theory, where the Indonesian people, as the principal, delegate authority to the agent, Kominfo, related to ESO policies. The results of the NPF found economic narration from the Ministry of Communication and Information Technology. This narration contradicts the narrative of ESO’s policy with the goal of its existence, which is the realization of digital sovereignty. This study also underscores the importance of co-regulation with ESO to strengthen the narrative of digital sovereignty.